Effect of 2 Day vs. 3 Day Superstimulation Protocol on In Vivo Maturation of OPU derived oocytes in Buffaloes - Singh, Narinder; Mavi, Gurjot Kaur; Kumar, Ajeet; V S Malik, (The Indian Journal of Animal Reproduction, 2023)
The study was planned to evaluate effect of two different superstimulation protocols (2 Day vs. 3 Day) on in vivo maturation of oocytes in buffaloes. Buffaloes (n=8) were superstimulated twice using 2x2 design at an interval of 30-35 days using 200 mg and 300 mg FSH divided into four and six tapering doses (each dose of 50 mg) given over 2 and 3 days at 12 hourly intervals. Prostaglandin F2α analogue (500 μg Cloprostenol; i/m) at 72 and 84 hrs after start of superstimulatory treatment. Oocytes were retrieved from > 6 mm follicles at 48 h after the last FSH injection by ovum pick up. Oocyte maturation was assessed by the degree of cumulus cell expansion and by Orcein staining of denuded oocytes. OPU of 60 and 91 follicles resulted in recovery of 38 and 50 cumulus oocyte complexes (COCs) in 2-Day and 3-Day group, respectively. Significantly higher proportion of expanded oocytes was recovered in 3-Day protocol compared to 2-Day protocol (36.0% vs. 13.2%) and higher number of compact COCs were recovered in 2-Day protocol. In 3-Day protocol, significantly higher percentage of oocytes retrieved was at Metaphase-II stage compared to 2-Day protocol (40% vs.15.8%, respectively). The preliminary trial demonstrated that 3-day superstimulatory protocol yielded higher percentage of in vivo matured oocytes than 2-Day protocol in buffaloes.
Keywords: Buffalo; Oocyte; Ovum pick-up; Superstimulation